2017
DOI: 10.4103/ijdr.ijdr_118_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of knowledge, awareness, and attitude toward emergency dental trauma management among the school teachers of Kolkata

Abstract: Despite the lack of knowledge and awareness regarding management of dental trauma, school teachers of Kolkata had a good attitude toward management of dental trauma and its education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
4
6
1
7
Order By: Relevance
“…Bakarcic et al ( 5 ) in their survey conducted on Croatian teachers, showed that 93% of students did not receive any formal training on this subject, yet over 87.0% of them were willing to participate in the training on such a subject. Similar results regarding the teacher population were obtained in other countries ( 28 , 29 ).…”
Section: Discussionsupporting
confidence: 88%
“…Bakarcic et al ( 5 ) in their survey conducted on Croatian teachers, showed that 93% of students did not receive any formal training on this subject, yet over 87.0% of them were willing to participate in the training on such a subject. Similar results regarding the teacher population were obtained in other countries ( 28 , 29 ).…”
Section: Discussionsupporting
confidence: 88%
“…Este índice foi semelhante ao trabalho de Chandukutty et al 2017, o qual verificou que 23,4% da população estudada procuraria imediatamente o cirurgião dentista. Esses dados estão confrontantes aos encontrados por Mori et al (2007), Alsadhan et al (2018) e Kaul et al (2017), os quais verificaram índices acima de 60%. Vale ressaltar que 49,4% dos participantes da presente pesquisa acalmariam o acidentado e procurariam o pronto-socorro, e 3% encaminhariam para hospitais; estes dados podem indicar que muitos dos participantes compreendem a importância do atendimento de urgência ao traumatismo dentário, e que os mesmos podem concluir que nestes ambientes há a presença de cirurgião dentista.…”
Section: Discussionunclassified
“…Vale ressaltar que 49,4% dos participantes da presente pesquisa acalmariam o acidentado e procurariam o pronto-socorro, e 3% encaminhariam para hospitais; estes dados podem indicar que muitos dos participantes compreendem a importância do atendimento de urgência ao traumatismo dentário, e que os mesmos podem concluir que nestes ambientes há a presença de cirurgião dentista. Ao comparar as respostas entre os participantes que já tiveram experiência com traumatismo dentário e os não experientes, pode-se verificar ausência de diferença entre as condutas, ao contrário do que foi observado por Kaul et al (2017). Cerca de 60% dos participantes da presente pesquisa relataram não ter sequelas ou as terem resolvido com tratamentos posteriores ao traumatismo; assim, acredita-se que isto pode ter influência na experiência, e que o traumatismo não promova grandes sequelas aos pacientes acometidos.…”
Section: Discussionunclassified
See 2 more Smart Citations